Inverse Parameter Identification for Orthotropic Elasto-Plastic Sheet-Steel - Söhngen, Benjamin; Willner, Kai (Proceedings in Applied Mathematics and Mechanics, 2015)
In this contribution the Finite Element Model Updating (FEMU) approach is utilized to determine the material parameters of sheet-steel. From experimental testing it is observed that the considered cold-rolled steel exhibits orthotropic behaviour. To regard this in the simulation, a user-implemented material model based on a quadratic yield function is used. Via the method of digital image correlation (DIC), the displacement field of a biaxially loaded specimen is measured from images taken at different stages of loading. Comparing the experimentally determined displacements to those obtained by simulation an error measure is defined which can be minimized by optimization algorithms. Starting with initial values for the orthotropic elasto-plastic material parameters, the FEM model is thus updated consecutively until a specified error margin is reached. (© 2015 Wiley-VCH Verlag GmbH & Co. KGaA, Weinhei
Keywords: Anisotropic Plasticity; Inverse Parameter Identification; FEMU